2021
DOI: 10.3390/microorganisms9051060
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Composition of SCOBY Starter Cultures Used by Commercial Kombucha Brewers in North America

Abstract: Kombucha fermentation is initiated by transferring a solid-phase cellulosic pellicle into sweetened tea and allowing the microbes that it contains to initiate the fermentation. This pellicle, commonly referred to as a symbiotic culture of bacteria and yeast (SCOBY), floats to the surface of the fermenting tea and represents an interphase environment, where embedded microbes gain access to oxygen as well as nutrients in the tea. To date, various yeast and bacteria have been reported to exist within the SCOBY, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
54
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 94 publications
7
54
0
2
Order By: Relevance
“…Consistent with prior studies, we found that Brettanomyces was the predominant yeast in five of the kombucha products [ 35 , 42 ]. However, the three other common yeast genera present in kombucha cultures ( Zygosaccharomyces , Lachancea and Starmerella ) were largely undetected in the nine kombucha products [ 35 ]. Instead, two products and one sample of a third product showed predominance of Cyberlindnera jadinii .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with prior studies, we found that Brettanomyces was the predominant yeast in five of the kombucha products [ 35 , 42 ]. However, the three other common yeast genera present in kombucha cultures ( Zygosaccharomyces , Lachancea and Starmerella ) were largely undetected in the nine kombucha products [ 35 ]. Instead, two products and one sample of a third product showed predominance of Cyberlindnera jadinii .…”
Section: Discussionsupporting
confidence: 92%
“…Bacillus coagulans has many known effects on health and has been commonly added to foods due to its heat resistance [ 18 ]. Many studies have reported that acetic acid bacteria were more commonly found in kombucha products than lactic bacteria, with a study of over 100 commercial kombucha starter cultures reporting that Komagataeibacter was most prevalent and abundant [ 1 , 33 , 34 , 35 ]. Lactic acid bacteria (primarily Lactobacillus ) are less commonly used in kombucha fermentation to enhance its biological function or added as probiotics [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Zhao and Sui (2018) identified Saccharomyces cerevisiae and Arxula adeninivorans as major yeast strains, while Komagataeibacter saccharivorans (formerly Gluconacetobacter saccharivorans), Acetobacter sp., Komagataeibacter europaeus (formerly Gluconacetobacter europaeus), Acetobacter aceti and Limosilactobacillus fermentum (formerly Lactobacillus fermentum) where found as major bacterial representatives of Kombucha starter [64]. In the latest research on over 100 samples of Kombucha tea from North America, Komagataeibacter (K. europaeus, K. medellinensis, K. saccharivorans, K. nataicola, K. xylinus, K. rhaeticus), Acetobacter (A. senegalensis, A. tropicalis), Gluconobacter (G. oxydans), and Liquorilactobacillus nagelii were described as main bacteria, while Brettanomyces (B. bruxellensis and B. anomalus), Saccharomyces cerevisiae, Saccharomycodes ludwigii, Zygosaccharomyces bisporus, Starmerella davenpoortii, Schizosaccharomyces pombe were identified as yeast strains [65].…”
Section: Scoby Composition and Metabolic Acticitymentioning
confidence: 99%
“…Metagenomics studies also predicted opportunistic bacteria like Bacillus, Pseudomonas, etc. (Arikan et al, 2020;Villarreal-Soto et al, 2020;Barbosa et al, 2021;Harrison and Curtin, 2021), as well as bacteriophages and yeast viruses (Góes-Neto et al, 2021). There is a metabolic interplay between yeasts that convert sugar into monosaccharides and ethanol, in a liquid phase, and AAB that use glucose, fructose, and ethanol to produce organic acids and bacterial cellulose (BC), in a pellicle film phase (Villarreal-Soto et al, 2018).…”
Section: Kombucha Per Se: Echoes Of the Past Or Back To The Future Kombucha As A Multimicrobial Communitymentioning
confidence: 99%